Dakwah KH Khoiron Syu’aib dalam Mendukung Transisi Karir Eks PSK di Eks Lokalisasi Bangunsari Surabaya - Fatin, Risma Azzah (Journal of Society and Development, 2023)
This research investigates the da'wah strategies employed by KH Khoiron Syu’aib in supporting the career transition of former commercial sex workers (PSK) in the Bangunsari area, Surabaya. A qualitative case study approach was used, focusing on interviews, observations, and documentation. The research was conducted in the former Bangunsari localization area, involving KH Khoiron Syu’aib, former PSK, and local community members. The study reveals that KH Khoiron Syu’aib's da'wah approach is holistic, integrating humanistic, habituation, and skill-training strategies. These approaches are instrumental in helping former PSK transition to more dignified and sustainable careers. The findings highlight the importance of a comprehensive da'wah approach that goes beyond spiritual guidance to include practical skill development and psychosocial support, offering a model for similar rehabilitation efforts in other regions. This research contributes to the understanding of how da'wah can effectively support social rehabilitation and empowerment, particularly in contexts involving vulnerable groups like former PSK.